Strategic Tower Defence Game - Dhinakar Gogi; Aditya Jadhav; Nayan Shingare; Joel Thomas; Dakshayani G (International Journal of Engineering and Management Research, 2021)
This research is based on intelligent strategy game known as Tower Defence in which players have to make strategic decisions to defend their tower from their enemies. This an interesting game where people can test their wits. In this game the players can build and upgrade their tower to prevent higher damage from enemies. This game requires quick strategic decisions and is fun to play. There are wide array of weapons/equipments that the player can access by using earning points. This game is developed by using Unity platform using C#. This game is easy and understandable as compare to other tower defence games available in market and can be played by players of all age. This intelligent strategy game is highly competitive and will help sharpen your brain too.